Agritourism: A Strategic Pathway for Development in Central America and the Caribbean - Arguelles González, Vivian (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
A workshop is held at the Canada Agriculture and Food Museum, highlighting agritourism as a blend of agriculture and tourism that offers visitors an immersive and educational experience in rural environments. The workshop took place both in-person and virtually and had 163 participants. One of the main objectives of the workshop was to promote a collaborative environment among stakeholders from various sectors. The workshop included two panels: the first, "Beyond the Beach: Exploring Agritourism Opportunities in the Caribbean," which featured the launch of the Caribbean Agritourism Network website by IICA; the second panel focused on "Public Policies for Agritourism and Demand in the Canadian Market." Additionally, there was a roundtable discussion on Agritourism Perspectives from SICA Countries.